Life history trade-offs are influenced by the diversity, availability and interactions of dietary antioxidants - Catoni, Carlo; Peters, Anne; Martin Schaefer, H. (Animal behaviour, 2008)
The expression of most life history traits, such as immunity, growth and the development of sexual signals, is negatively affected by high levels of oxidative stress. Dietary antioxidants can reduce oxidative stress and have therefore been the focus of numerous studies in behavioural and evolutionary ecology in the last few decades. Most of this research has focused on carotenoids, neglecting a number of more common, more potent, and thereby potentially more important, antioxidants, such as polyphenolic antioxidants. However, the effects of several classes of antioxidants on different life history traits have been thoroughly investigated in medical and animal-breeding studies. We suggest that behavioural and evolutionary studies will benefit from incorporating these advances. By reviewing the literature on the effects of antioxidants on life history traits in fish, birds and mammals, we develop a broad framework for dietary antioxidants. Fundamental properties of antioxidants, in particular their biochemistry, their potency and the interactions between them affect their relative relevance for life history traits. Based on tissue affinity, we distinguish between two categories of dietary antioxidants: focal antioxidants that are intrinsically important for a given trait and nonfocal antioxidants that influence traits only indirectly. Furthermore, we show how temporal and spatial environmental variability in antioxidant availability, as well as individual variation in food selection, may generate interindividual differences in the expression of life history traits. Finally, we suggest future research lines and experimental designs that may provide basic information needed to advance our knowledge of the ecological and evolutionary relevance of dietary antioxidants.